Agreement between direct, oscillometric and Doppler ultrasound blood pressures using three different cuff positions in anesthetized dogs - Garofalo, Natache A. [UNESP]; Teixeira Neto, Francisco José [UNESP]; Alvaides, Renata K. [UNESP]; de Oliveira, Flavia A. [UNESP]; Pignaton, Wangles [UNESP]; Pinheiro, Renato T. [UNESP] (Wiley-Blackwell, 2012)
Objective To evaluate the agreement between invasive blood pressure (IBP) and Doppler ultrasound blood pressure (DUBP) using three cuff positions and oscillometric blood pressure (OBP) in anesthetized dogs.Study design Prospective study. Animals Nine adult dogs weighing 14.5-29.5 kg.Methods The cuff was placed above and below the tarsus, and above the carpus with the DUBP and above the carpus with the OBP monitor. Based on IBP recorded via a dorsal pedal artery catheter, conditions of low, normal, and high systolic arterial pressures [SAP (mmHg) <90, between 90 and 140, and >140, respectively] were induced by changes in isoflurane concentrations and/or dopamine administration. Mean biases +/- 2 SD (limits of agreement) were determined.Results At high blood pressures, regardless of cuff position, SAP determinations with the DUBP under-estimated invasive SAP values by more than 20 mmHg in most instances. With the DUBP, cuff placement above the tarsus yielded better agreement with invasive SAP during low blood pressures (0.2 +/- 16 mmHg). The OBP underestimated SAP during high blood pressures (-42 +/- 42 mmHg) and yielded better agreement with IBP for mean (MAP) and diastolic (DAP) arterial pressure measurements [overall bias: 2 +/- 15 mmHg (MAP) and 0.2 +/- 16 mmHg (DAP)].Conclusions Agreement of SAP determinations with the DUBP is poor at SAP > 140 mmHg, regardless of cuff placement. Measurement error of the DUBP with the cuff placed above the tarsus is clinically acceptable during low blood pressures. Agreement of MAP and DAP measurements with this OBP monitor compared with IBP was clinically acceptable over a wide pressure range.Clinical relevance With the DUBP device, placing the cuff above the tarsus allows reasonable agreement with IBP obtained via dorsal pedal artery catheterization. Only MAP and DAP provide reasonable estimates of direct blood pressure with the OBP monitor evaluated.
Keywords: arterial blood pressure; dogs; doppler; non-invasive blood pressure; oscillometry